SISTEM INFORMASI GEOGRAFIS GOA DI JAWA TENGAH BERBASIS WEB - Maulana, Taufik; Sholeh, Mohammad; Hamzah, Amir (Jurnal Script, 2015)
ABSTRACTSystem information is information technology which is currently growing so pesat.Teknologi that can help more easily, quickly, safely and effectively clear it is helpful to anyone who use it. Including to assist the community in search of the cave. While doing caving cave information need to be visited is very important, considering the tourists who conduct tours of the cave there are some dangerous cave visited in the area. And it makes the problem of how travelers can search for suitable cave, given some constraints such as do not know the area, or do not have a friend who can show cave Goad an appropriate state for the tourists. This information system that will accommodate for tourists caves that are confused in finding the appropriate information and the cave that will help determine the state of a focused Online.sistem cave in cave information, place and circumstances of the cave can be done with this system. The success of the implementation of this system is that it can run well to help the tourists cave within a cave looking for suitable locations. By using geographic information systems make more effective web boarding and search, directions, until the state of the cave online that facilitates the process of selecting the cave to be visited.Â Key Words: Information ,system,Geographic, Cave.